MODERN APPROACHES TO THE DIAGNOSIS AND TREATMENT OF ENDOCERVICITIS AND COLPITIS IN PREGNANT WOMEN - Arazmuhamedova S.; Scientific Supervisor: Ismoilova D.O. (Web of Journals Publishing, 2025)
This article analyzes modern approaches to the diagnosis and treatment of endocervicitis and colpitis during pregnancy. Endocervicitis and colpitis are inflammatory diseases of the reproductive tract, which are more commonly observed during various stages of pregnancy. These conditions pose a serious threat to maternal health and may adversely affect fetal development. Therefore, early diagnosis and appropriate treatment are crucial to ensure a healthy pregnancy. The article explores the effectiveness of modern laboratory tests and microscopic examinations for diagnosing endocervicitis and colpitis, as well as the application of microbiological and molecular diagnostic methods. In addition, the importance and effectiveness of combining antibiotics, antifungal agents, and immunomodulators in treatment are discussed in detail. The article provides a comprehensive overview of the development of modern diagnostic approaches and effective treatment strategies for endocervicitis and colpitis during pregnancy. The study results demonstrate that these pathologies can be effectively managed through advanced diagnostic and therapeutic methods.
Keywords: Pregnancy, endocervicitis, colpitis, diagnosis, treatment, modern approach, microscopy, antibiotics, antifungal agents.